Advances in Nanoliposomes Production for Ferrous Sulfate Delivery - Sabrina Bochicchio; Annalisa Dalmoro; Gaetano Lamberti; Anna Angela Barba (MDPI AG, 2020)
In this study, a continuous bench scale apparatus based on microfluidic fluid dynamic principles was used in the production of ferrous sulfate-nanoliposomes for pharmaceutical/nutraceutical applications, optimizing their formulation with respect to the products already present on the market. After an evaluation of its fluid dynamic nature, the simil-microfluidic (SMF) apparatus was first used to study the effects of the adopted process parameters on vesicles dimensional features by using ultrasonic energy to enhance liposomes homogenization. Subsequently, iron-nanoliposomes were produced at different weight ratios of ferrous sulfate to the total formulation components (0.06, 0.035, 0.02, and 0.01 w/w) achieving, by using the 0.01 w/w, vesicles of about 80 nm, with an encapsulation efficiency higher than 97%, an optimal short- and long-term stability, and an excellent bioavailability in Caco-2 cell line. Moreover, a comparison realized between the SMF method and two more conventional production techniques showed that by using the SMF setup the process time was drastically reduced, and the process yield increased, achieving a massive nanoliposomes production. Finally, duty-cycle sonication was detected to be a scalable technique for vesicles homogenization.